Milton Shain, A Perfect Storm: Antisemitism in South Africa, 1930–1948 (Historia, 2021)
Milton Shain is without a doubt one of South Africa’s best historians. He needs no introduction and made a lasting contribution to Jewish Studies in South African history through a long and prosperous career. I first encountered his scholarship when I read his book, The Roots of Anti-Semitism in South Africa, published in 1994. This book also won the UCT book prize in 1996, and not without merit. I was again reminded of his erudite ability to identify a historical tendency and trace its trajectory within diverse and intersecting discourses of the past when I read his latest book, A Perfect Storm: Antisemitism in South Africa, 1930-1948.
Keywords: Jewish Studies; Anti-Semitism; United Party; 1930 Quota Act; D.F Malan; Greyshirts; National Party